Development of Interactive E-module Based on Infographic Multimedia In Islamic History Of Indonesian Courses As An Innovative Learning Source - Ricu Sidiq; N Najuah; Pristi Suhendro Lukitoyo; Josia Parlindungan Manalu; Zulfahdilla Elvansya (CV. Inara, 2022)
In this semester, in the atmosphere of the Covid 19 pandemic, innovative learning resources are needed to improve the quality of learning. This research has the purpose of making an interactive e-module product based on multimedia infographics for the History of Indonesia during the Islamic Period course. The methods used are the research method and development method or Research & Development (R&D). The research was implemented to 2019 batch students of the History Education Department. The research stages used are the Borg and Gall methods. The technique of collecting data is using a form of questionnaire or questionnaire, then the technique of data analysis is using the calculation of percentages and averages. The results of this research indicate that the validation of the material and the media expert obtained a percentage score of 93% and 82%, respectively. Meanwhile, the results of small and medium-scale product trials showed a percentage score of 89% and 86%, respectively. Then, the results of the large-scale use trial and effectiveness test showed a percentage score of 85.6% and 79.4%, respectively. With these results, it can be concluded that the interactive e-module based on multimedia infographics is very valid, so it is feasible and effective to use in the learning process. The limitations of the research product are that the file size is too large, the uniqueness of the research product is that one download can be used offline on a cellphone or computer so as possible to save the internet data.